The effects of lower-body compression garments on recovery between exercise bouts in highly-trained cyclists - Driller, M. W.; Halson, S. L. (Journal of Science and Cycling, 2013)
The use of compression garments as a recovery strategy has become popular amongst athletes. The aim of the current study was to investigate the effect of lower-body compression garments on recovery between two cycling bouts. Ten highly-trained cyclists (mean ± SD; age = 31 ± 6 years; height = 181 ± 6 cm; mass = 75.9 ± 5.9 kg; VO2peak = 66.6 ± 3.8 mL/kg.min) performed two 30-minute cycling bouts (15-minutes at a fixed power output, 15-minute time-trial) on a cycle ergometer, separated by a 60-minute passive recovery period where either lower-body compression garments (LBCG) or loose-fitting shorts (CON) were worn. Subject`s performed both trials in a randomized, crossover design separated by three days. Blood lactate, leg girths and perceived soreness was measured throughout the recovery period. Results indicated a small but significant improvement (P < 0.05) in recovery as evidenced by the maintenance of power output in the second exercise bout in the LBCG trial when compared to the CON trial (-0.20% and -2.15%, respectively. Effect Size (ES); 0.22). LBCG were also associated with significant reductions in limb girths and blood lactate concentration when compared to CON. While not statistically significant, there was a moderate effect on perceived soreness in the LBCG trial (ES; -0.62). We would suggest that lower-body compression garments enhance recovery between cycling bouts and improve subsequent performance.